Exploratory experiment on fertilization of five tropical legumes on a soil from a "cerrado" area - França, Gonçalo E. de; Carvalho, Margarida M. de (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse experiment was carried out to investigate nutrient deficiencies which restrict the development of the legumes: Glycine javanica L. (var. comum), Glycine javanica (var. tinaroo), Phaseolus atropurpureus D.C. (siratro), Pueraria javanica Benth. (kudzu tropical) and Centrosema pubescens Benth., on a red-latosol "fase cerrado". The results obtained led to the following conclusions: a) Individual legume response was different in relation to the deficiencies presented by the "cerrado" soil; b) The large phosphorus deficiency presented by this soil caused a decrease in nodule weight and in nitrogen and dry matter yields of all legumes; c) Ommission of both potassium and sulfur failed to cause any negative effect on dry matter yield or nitrogen fixation; d) The accentuated micro-element deficiency which seriously affected the tinaroo variety of Glycine javanica, had almost no effect on the siratro variety; e) All legumes were seriously affected by omission of liming, which caused a decrease in both dry matter yield and nitrogen fixation, and increased production of ineffective nodules, especially in kudzu and Centrosema; f) Application of nitrogen fertilizer decreased nodule weight, but increased total nitrogen in the plant. Total nitrogen fixed in the five legumes ranged from 53 to 83% of the nitrogen assimilated by the plants receiving mineral nitrogen.